Analisis Social Return on Investment (SROI) UMKM Kripik Jamur Tiram Desa Talang Kering melalui Program Tanggung Jawab Sosial (TJSL) PT. PLN Sumbagsel - Rindang Matoati; Praningrum Praningrum; Popi Puspita; Imron Rosyadi (IPB University, 2023)
A company's success in achieving sustainable business success is not just seen in terms of business profits, but should also pay attention to The Triple Bottom Line. The investment made by the company is not just physical, but social and environmental, which is done through the corporate social responsibility program. PT. PLN (Persero) UIP Sumbagsel implements the CSR program by providing funds intended for working capital and licensing to the Micro, Small and Medium Enterprise (MSME) group who process oyster mushroom chips in Talang Dry Village, North Bengkulu. The purpose of this study was to carry out data collection, evaluation, calculation of the impact of social return on investment (SROI) on the implementation of the PT. PLN CSR program, for MSMEs Processing Oyster Mushroom Chips located in Talang Dry Village, North Bengkulu Regency, Bengkulu Province. The results of the SROI analysis of CSR by PT. PLN has managed to bring economic, social and environmental advantages.